Encyclopedia of Tourism Management and Marketing 2022
DOI: 10.4337/9781800377486.evidence-informed.planning
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-informed Planning for Tourism

Abstract: The purpose of this paper is to further advance the discussion regarding Local Authorities and approaches to facilitate sustainable planning for tourism. Building on previous research into tourism planning at local level in Ireland, this study employed qualitative semi-structured interviews with every senior planner in Ireland's 28 Local Authorities to identify the degree to which evidenceinformed planning for tourism is encouraged. Findings point to a tendency from senior planners to rely on existing legislat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Discussions concerning the sustainability agenda for destinations still revolve around the challenges of monitoring growth limits and managing capacities [4,18,28]. McLoughlin and Hanrahan [8] argue that such concerns can be addressed by applying reliable tourism indicator systems [7,29,30]. However, applying these systems by Local Authorities remains a relatively under-researched topic.…”
Section: Sustainable Tourism Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Discussions concerning the sustainability agenda for destinations still revolve around the challenges of monitoring growth limits and managing capacities [4,18,28]. McLoughlin and Hanrahan [8] argue that such concerns can be addressed by applying reliable tourism indicator systems [7,29,30]. However, applying these systems by Local Authorities remains a relatively under-researched topic.…”
Section: Sustainable Tourism Managementmentioning
confidence: 99%
“…Maxim [39] further alluded to their legal responsibility for providing planning guidelines for tourist services after examining sustainable tourism planning by Local Authorities in London. However, moving towards an evidence-based approach to tourism planning depends on using quality indicators but also on the effectiveness and commitment of policy makers to apply them effectively and accurately [7,40].…”
Section: Sustainable Tourism Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evidence has shown that tourism has not always met destination development expectations [4,5]. Effective planning with a sustainable long-term vision is vital for long-term economic and social development, visitor satisfaction, improved business success, social integration, and the protection of environmental assets [6,7]. McLoughlin and Hanrahan [8] and Mason [9] note how tourism planning is crucial to delivering on a destination's sustainability agenda.…”
Section: Introductionmentioning
confidence: 99%